2003
DOI: 10.1002/ceat.200301836
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Chemical Reactions

Abstract: This article reviews the state of the art of microwave-assisted reactions and the influence of microwaves on mass and heat transfer. The heating behavior of representative test reactions and single substances is compared for heating with microwaves and thermal energy. Similarities and differences between convective heating and dielectric irradiation methods are discussed with regard to the yield, the selectivity, and the enantiomeric purity of the reaction products. Furthermore, prevailing problems related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…Studies have shown that the pretreatments performed at high temperature have given successful results, in increasing the hydrolysis rate and product yields, while decreasing the residence time and reagent or chemical concentration required [2], [59], [86], [87]. This temperature increment may be performed by conventional heating or by using microwave radiation, which has some advantages over the conventional heating like, superficial heat transfer, no direct contact of heating source and material, providing a volumetric and rapid heat and selective heating of more polar part and creating a hot spot with inhomogeneous materials [2], [16], [19], [41], [46], [70], [103]. Figure-3 shows a comparative analysis between conventional heating and microwave heating [100].…”
Section: Microwave Pretreatmentmentioning
confidence: 99%
“…Studies have shown that the pretreatments performed at high temperature have given successful results, in increasing the hydrolysis rate and product yields, while decreasing the residence time and reagent or chemical concentration required [2], [59], [86], [87]. This temperature increment may be performed by conventional heating or by using microwave radiation, which has some advantages over the conventional heating like, superficial heat transfer, no direct contact of heating source and material, providing a volumetric and rapid heat and selective heating of more polar part and creating a hot spot with inhomogeneous materials [2], [16], [19], [41], [46], [70], [103]. Figure-3 shows a comparative analysis between conventional heating and microwave heating [100].…”
Section: Microwave Pretreatmentmentioning
confidence: 99%
“…It was determined from an extensive series of energy efficiency assessments of microwave-assisted syntheses that no immediate increase in efficiency compared to conventional reactions was observed [23].…”
Section: Power Input Power Measurement and Data From Manufacturersmentioning
confidence: 99%
“…We thus opted to evaluate their application to BSG, due to their relative simplicity, and hence cost-effectiveness. Microwave irradiation (dielectric heating) offers an alternative method for the rapid and controlled generation of heat within materials [24,25], to stimulate hydrothermal reaction conditions. It has also been speculated that rapid internal heating of water distributed throughout a lignocellulosic material could help to disrupt that structure effectively.…”
Section: Introductionmentioning
confidence: 99%